First Supramolecular Complexes of Organotin(IV) with Kryptofix 5: Synthesis and Spectral Study - Yousefi, Mohammad; Tavakolinia, Fatemeh (Asian Journal of Chemistry, 2011)
Four novel organotin(IV) complexes of kryptofix 5 with general formula [(R2SnCl2)2(L)], R = Me(1), Ph(2), Bz(3), [(R3SnOCOCF3(L)], R = Ph(4), L = kryptofix5, have been prepared. The newly synthesized compounds have been characterized by UV-VIS, FT-IR, multinuclear NMR (1H, 13C and 119Sn, 19F) and mass spectrometry. The J = 80 and 120 of methyl group of complex (1) and (4) indicate five and higher than five coordinated central tin atom.